The relationship between leg muscle strength, balance, and shooting accuracy in futsal players - Nur Hakim, Muhammad Reza; Solihin, Akhmad Olih; Syamsudar, Bangbang (Universitas Tanjungpura, 2025)
Background. Despite the physical demands of futsal, the combined effect of leg strength and balance on shooting accuracy remains underexplored, highlighting the need for integrated training based on observed performance gaps in youth players. Objectives. This study investigates the relationship between leg muscle strength and balance with shooting ability in futsal, emphasizing their combined impact on performance. Methods. A quantitative correlational research design was used, involving 20 high school futsal players selected through total sampling. Three measurement tests were conducted: a leg muscle strength test, a balance test, and a shooting ability test. Data analysis included Karl Pearson